2008
DOI: 10.1007/s00405-008-0868-5
|View full text |Cite
|
Sign up to set email alerts
|

The HD-Panoramic Visualization System: a new visualization system for ENT surgery

Abstract: This work examines the application possibilities of a new visualization system, the Panoramic Visualization System (HD-PVS), in ENT surgery. The Panoramic Visualization System (PVS) is a novel optical system that is neither an endoscope nor a microscope. It has a focal length of 200 mm, a wide field of view and is used together with an HD camera and an HD monitor (HD-PVS). The analysis of the visualization quality took place in laboratory conditions using 4 close-to-surgery scenarios with altogether 40 data po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…15 Several other surgeons have used the VITOM Ò for spinal surgery, vascular and cardiac surgery, ENT surgery, hepatic surgery, and experimental small animal surgery. 16 In most of these settings, the VITOM Ò has provided high quality imaging and facilitated surgical resection as an alternate to the operating microscope or loupes. In general, the VITOM Ò has proven extremely useful when the surgical field is largely perpendicular to the line of site of the surgeon because the anatomy can be well-visualized and the surgeon operating from the monitor maintains a head position similar to that with the microscope.…”
Section: Discussionmentioning
confidence: 99%
“…15 Several other surgeons have used the VITOM Ò for spinal surgery, vascular and cardiac surgery, ENT surgery, hepatic surgery, and experimental small animal surgery. 16 In most of these settings, the VITOM Ò has provided high quality imaging and facilitated surgical resection as an alternate to the operating microscope or loupes. In general, the VITOM Ò has proven extremely useful when the surgical field is largely perpendicular to the line of site of the surgeon because the anatomy can be well-visualized and the surgeon operating from the monitor maintains a head position similar to that with the microscope.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, both the operating microscope and exoscope were used. A further paper by Minoda and Miwa 13 described two cholesteatoma cases undertaken using a combination of endoscope and exoscope. Finally, Rubini et al 9 described a series of 12 patients undergoing a wide range of lateral skull base surgery using the Storz Vitom exoscope and compared the results with 12 patients undergoing similar surgery using a microscope.…”
Section: Discussionmentioning
confidence: 99%
“…Limited trials of exoscope use in neurosurgery and otolaryngology have indicated benefits with regard to surgical ergonomics, compact size, and image quality. [1][2][3] Indeed, otolaryngologists are at risk for work-related neck and back pain that is thought to be due, in part, to prolonged microscope usage. 4 A monitor-based display that liberates surgeons from needing to conform to line-of-sight binocular eyepieces could eliminate a potential source of detrimental surgical ergonomics.…”
mentioning
confidence: 99%